Parent-adolescent intergenerational transmission of distress: the roles of family climate, adolescents’ self-compassion and mindfulness - Zhou, Shuying; Kwan, Chi Kin; Ai, Yueyue; Ma, Ying (Frontiers in Psychology, 2025)
BackgroundExisting research indicates that parental psychological distress correlates with adverse psychological outcomes in adolescents. Nevertheless, limited studies have delved into the mechanisms underpinning this relationship.ObjectivesThis study aimed to examine whether the link between parental psychological distress and adolescent psychological distress is mediated by the family emotional climate, as well as adolescents’ mindfulness and self-compassion.MethodsThe study sample consisted of 348 parent-adolescent dyads. Adolescents (57.5% female) had a mean age of 14.21 years (SD = 1.74, age range: 12–18 years). Parents reported their psychological distress, while adolescents completed measures of family emotional climate, mindfulness, self-compassion, and psychological distress.ResultsThe results indicated that parents’ psychological distress was indirectly linked to adolescents’ psychological distress via the family emotional climate, adolescent mindfulness, and self-compassion. Furthermore, the path models were found to be invariant across different age stages and sexes of adolescents.ConclusionMindfulness and self-compassion appear to develop within a family emotional environment marked by care and harmony. These two personal resources, in conjunction with parents’ psychological distress, are associated with adolescents’ psychological distress.